Scenarios for the future of the German confectionary market by 2030 - strategic implications for Ferrero Germany: sweet symphony narrative and strategy - Weber, Chantal Valerie (2023)
This work project explores the future of the German confectionery market employing the ‘Intuitive Logics School’ of scenario planning. The report focuses on extensive expert and client involvement, particularly collaborating with Ferrero Deutschland GmbH. The primary objective is to navigate high uncertainty, understand plausible events' impacts on industry, retail, and consumers, and dynamically respond to an unknown future. The development of four plausible scenarios centered on the key uncertainties ‘Stability of Supply Chain’ and ‘Health Regulations’, contributes to fostering a heightened awareness. The reader is introduced to one of four potential futures for the German confectionery market. This particular future is distinguished by a stable supply chain and health regulations that align with present norms. Scenario-specific strategic implications and a comprehensive strategic action plan tailored for Ferrero Deutschland GmbH are provided.